Extracranial stereotactic body radiotherapy in oligometastatic or oligoprogressive breast cancer - Weykamp, Fabian; König, Laila; Seidensaal, Katharina; Forster, Tobias; Hoegen-Saßmannshausen, Philipp; Akbaba, Sati; Mende, Stephan; Welte, Stefan Ezechiel; Deutsch, Thomas M.; Schneeweiss, Andreas; Debus, Jürgen; Hörner-Rieber, Juliane (Frontiers in oncology, 2020)
Oligometastatic disease (OMD) and oligoprogressive disease (OPD) describe tumor states with a limited metastasization. In contrast to other disease states, treatment of OMD or OPD has not yet become common for breast cancer. We sought to understand the outcomes and toxicities of this treatment paradigm. We retrospectively analyzed female breast cancer patients with OMD (≤3 metastases) or OPD (1 progressive lesion) who received stereotactic body radiotherapy (SBRT) for their respective extracranial metastatic lesions between 01/2002 and 07/2019. Survival analysis was performed using the Kaplan-Meier method with log-rank test being used for evaluation of significance. Cox regression was used to detect prognostic outcome factors. Toxicity was evaluated using the Common Terminology Criteria for Adverse Events (CTCAE v. 5.0). Forty-six patients (70% OMD; 30% OPD) with 58 lesions met criteria for inclusion. The majority of treatments (34 out of 58; 58.6%) were delivered from 2017 to 2018. Treatment sites were bone, liver, lung (n=19 (33%) for each site), and adrenal gland (n=1 (1%)). Median biologically effective dose (BED at α/β=10) was 81.6Gy (range: 45-112.5Gy) and median planning target volume was 36.60mL (range: 3.76 - 311.00mL). At 2-years, local control (LC) was 89%, distant control (DC) was 44%, progression free survival (PFS) was 17% and overall survival (OS) was 62%. Multivariate analysis identified the diagnosis of a solitary metastasis as an independent prognostic factor for superior DC (HR=0.186, CI [0.055; 0.626], p=0.007) and PFS (HR=0.363, CI [0.152; 0.863], p=0.022). OS was independently inferior for patients treated at a higher age (HR=5.788, CI [1.077; 31.119] p=0.041). Nine (15.5%) grade I° and one (1.7%) grade II° toxicities were recorded, with no grade III° or higher toxicities. Extracranial SBRT in breast cancer patients with OMD or OPD was well tolerated with excellent LC. SBRT should especially be offered to younger OMD and OPD breast cancer patients with only one metastasi s. The increase in utilization since 2017 points towards a growing acceptance of SBRT for OMD and OPD in breast cancer.
Gesehen am 29.09.2020